Assessing The Role of Psyllium Husk for Sensory Impact on Taste, Aroma and Texture of Rice Krispy Cereal Bar Snack - Angrainy, Hanny; Chandra, Thalia; Tjahjono, Novita; Kurniawan, Maycella Sheren (Indonesian Journal of Life Sciences, 2024)
The cereal bars market has experienced significant growth due to the rise of the "snackification" trend,where snacks replace meals. Time constraints during meal occasions have led consumers to seek satisfyingsnacks like cereal bars, offering tailored nutrition solutions. Ingredients are not only affecting the nutritionalvalue of cereal bars, but also contributing to their sensory attributes, such as taste, aroma, and texture. Oneof the important ingredients in cereal bars is xanthan gum, which serves as a binding agent. Psyllium husk isa potential substitute for xanthan gum, enhancing cereal bar texture and acting as dietary fiber to enhancefeelings of fullness and facilitate healthy digestion. The objective of this study was to formulate cereal barswith functional properties, utilizing psyllium husk as an essential ingredient and understand its impact onsensorial properties on taste, aroma, and texture, comparing it to xanthan gum. Four types of samples wereexamined using 9-scale hedonic tests among 50 panelists to evaluate the degree of acceptance on thesensory attributes of cereal bars. Results of this study showed that formulations with psyllium husksurpassed those with xanthan gum in terms of aroma and taste, followed by hardness and chewiness,making them preferred choices for cereal bars.